1996
DOI: 10.1021/bi960248u
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Phosphorylation States of pp60c-src with Tyrosine Kinase Activity:  The Intramolecular pY530−SH2 Complex Retains Significant Activity If Y419 Is Phosphorylated

Abstract: Rapid digestion of pp60c-src tyrosine kinase (src TK) in combination with electrospray ionization mass spectrometry enabled the determination of the time course for autophosphorylation of three tyrosine sites (Y338, Y419, and Y530) and a correlation with src TK activity. A form of src TK was purified from baculovirus-infected cells which contains only Y338 partially phosphorylated. Incubation with MgATP increases the phosphorylation of all three sites. The autophosphorylation and dephosphorylation of Y419 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 19 publications
8
69
1
Order By: Relevance
“…The purpose of these experiments was to determine whether the C-terminal tail becomes disengaged from the SH2 domain after autophosphorylation on Tyr 416 . Previous experiments on Src demonstrated that a form of Src with an intramolecular interaction between the SH2 domain and the phosphorylated tail was able to autophosphorylate at Tyr 416 (9). We wished to address the question of whether autophosphorylation leads to a subsequent disruption of the SH2-tail interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of these experiments was to determine whether the C-terminal tail becomes disengaged from the SH2 domain after autophosphorylation on Tyr 416 . Previous experiments on Src demonstrated that a form of Src with an intramolecular interaction between the SH2 domain and the phosphorylated tail was able to autophosphorylate at Tyr 416 (9). We wished to address the question of whether autophosphorylation leads to a subsequent disruption of the SH2-tail interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of Tyr 527 by c-Src kinase (Csk) produces an intramolecular interaction between the phosphorylated tail and the SH2 domain that inhibits Src kinase activity (4 -7). Src can also autophosphorylate Tyr 527 , but it is not the primary autophosphorylation site (8,9). The major autophosphorylation site, Tyr 416 , lies in the activation segment, a flexible portion of the catalytic domain near the active site.…”
mentioning
confidence: 99%
“…Phosphorylation of Tyr-419/416 can also activate Src activity in the context of simultaneous phosphorylation at Tyr-530/527 (Boerner et al, 1996;Sun et al, 1998), suggesting that active Src phosphorylated at Tyr-419/416 can not be fully inactivated by phosphorylation at Tyr-530/527 alone. This supports the findings that inactive Src may be the target of other kinases that can phosphorylate Tyr-419/416 and cause Src activation (Chiang and Sefton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…vSrc) has more modest e ects (Snyder and Bishop, 1984;Snyder et al, 1983), suggesting that other alterations can perturb the normal regulatory processes imparted by the activation loop. Phosphorylation of Tyr(416/ 419) can also activate Src activity in the context of simultaneous phosphorylation at Tyr(527/530) (Boerner et al, 1996;Sun et al, 1998), suggesting ®rst, that active Src phosphorylated at Tyr(416/419) cannot be fully inactivated by phosphorylation at Tyr(527/530) alone, but also requires dephosphorylation of Tyr(416/ 419). Secondly, this supports recent ®ndings that inactive Src family members may be the target of other kinases that can phosphorylate Tyr(416/419) and cause their activation (Chiang and Sefton, 2000).…”
Section: Regulation Of C-src By Phosphorylationmentioning
confidence: 99%